2021
DOI: 10.3390/ijerph182413324
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Knowledge of Human Microbiota among University Students in Jordan, an Online Cross-Sectional Survey

Abstract: Human microbiota have a significant impact on the health of individuals, and reciprocally, lifestyle choices of individuals have an important effect on the diversity and composition of microbiota. Studies assessing microbiota knowledge among the public are lacking, although it is hypothesized that this knowledge can motivate healthier behavior. Hence, this study aimed to measure microbiota knowledge among university students, and the effect of this knowledge on behavioral beliefs. A descriptive cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Students in healthcare fields showed significantly better KAP scores than students from non-healthcare fields, which is unsurprising given their training and has been demonstrated in other related TB knowledge surveys ( 23 ). But unlike studies that found KAP levels to be associated with gender or age ( 24 , 25 ), this study found a better KAP score only in healthcare students and a worse practice score in smokers.…”
Section: Discussionmentioning
confidence: 61%
“…Students in healthcare fields showed significantly better KAP scores than students from non-healthcare fields, which is unsurprising given their training and has been demonstrated in other related TB knowledge surveys ( 23 ). But unlike studies that found KAP levels to be associated with gender or age ( 24 , 25 ), this study found a better KAP score only in healthcare students and a worse practice score in smokers.…”
Section: Discussionmentioning
confidence: 61%
“…Participants who took a microbiology course scored much higher on microbiota knowledge and were more aware of the impact of antibiotics on microbiota. The study demonstrates that spreading information about the microbiota and microbiology in general can enhance antibiotic use behavior 12 .…”
Section: Discussionmentioning
confidence: 85%
“…The demonstrated difference between the knowledge status of medical and non-medical survey participants was statistically significant ( p < 0.001). A study, from the same year conducted in Jordan by Abu-Humaidan et al [ 37 ], found that 39% of students ( n = 157) demonstrated an advanced level of knowledge regarding microbiota. In contrast, basic knowledge of the topic covered was characterized by 50% ( n = 202) of the respondents.…”
Section: Discussionmentioning
confidence: 99%